The economic and environmental efficiency assessment in EU cross-country: Evidence from DEA and quantile regression approach - Moutinho, Vítor (2018)
This article aims to estimate the efficiency of 26 different European Countries over 2001 and 2012 comparing their performance. Data Envelopment Analysis technique is used in a first step to evaluate the performance of each European country. The output-oriented model was used with two specifications (Variable and Constant Returns to Scale) including as inputs labour and capital productivity, the weight of fossil energy and the share of renewable energy in GDP (gross domestic product), being the output GDP per GHG (greenhouse gases) emissions. In a second step, the quantile regression technique was used, to explain different efficiency scores through variables as Environmental Taxes Revenues, Resources Productivity and Domestic Material Consumption. Results indicate that share of renewables and non-renewable energy sources are important to explain differences in emissions. They suggest a significant change in the trend of economic and environmental efficiency in European countries and put forward the high disparities existing among them. Policy recommendations point for the need of higher steps if the goal is to equal countries efficiency scores. Moreover, environmental tax revenue effects are negatively stronger in less efficient countries, whereas also exerting negative influence over those more eco-efficient. Transport taxes affect negatively more eco-efficient countries and positively less eco-efficient countries. Energy taxes only seem to positively influence the lower eco-efficient countries. There is also evidence for a negative premium of efficiency considering domestic materials consumption. Finally, resources productivity shows a positive and significant influence independently of the country technical eco-efficiency level.